(untitled) (Revista Puertorriqueña de Psicologia, 2019)
The purpose of this study was to evaluate observed parenting styles among Puerto Rican parents and understand the relationship between those styles and child outcomes. Participants included 51 families with a child between the ages of 6 and 11. Three parenting dimensions (i.e., warmth, demandingness, autonomy granting) were coded with the Parenting Style Observation Rating Scale. We used the Child Behavior Checklist to assess child behavioral problems. Overall, parents received high ratings on warmth, demandingness, and autonomy granting. Supportive demandingness was negatively associated with internalizing, externalizing, and total child problems. The majority of the sample was categorized as authoritative (68.6%), while 23.5% was categorized as cold. Authoritative parenting was significantly associated with lower child problems across the board in comparison to families categorized as cold or permissive. Limitations of the current study were considered. We discussed implications of the results and directions for future research in regard to Puerto Rican parenting for families living in Puerto Rico.